2011
DOI: 10.3892/ijmm.2011.859
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-1 in high glucose-induced epithelial-mesenchymal transition during peritoneal fibrosis

Abstract: Abstract. Peritoneal fibrosis is a major complication of continuous ambulatory peritoneal dialysis (CAPD). The present study tested the hypothesis that ADP-ribose polymerase-1 (PARP-1) may play a role in peritoneal epithelial-mesenchymal transition and fibrosis under high glucose conditions. High glucose (126 mmol/l)-induced peritoneal EMT and fibrosis via the PARP-1 mechanism was examined in the primary culture of rat peritoneal mesothelial cells (PMCs) and in the human peritoneal mesothelial cell line (HMrSv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Much research showed that HG could induce epithelial-mesenchymal transition and the loss of epithelial phenotype E-cadherin was involved in the progress [19, 20]. Our results also found that HG could decrease the expression of E-cadherin compared with LG in two PC cells.…”
Section: Discussionsupporting
confidence: 74%
“…Much research showed that HG could induce epithelial-mesenchymal transition and the loss of epithelial phenotype E-cadherin was involved in the progress [19, 20]. Our results also found that HG could decrease the expression of E-cadherin compared with LG in two PC cells.…”
Section: Discussionsupporting
confidence: 74%
“…All doses and times of these treatments were determined in our pre-experimental results and previous study. 47 As described above, MCs were then divided into the following groups for subsequent experiments: G5, G25, G25+PJ34, G25+EX527, G25+PJ34+EX527, G25+SIRT-1 lentivirus transfected (G25+Lv-SIRT-1), G25+SIRT-1 lentivirus trans-fected+PJ34 (G25+Lv-SIRT-1+PJ34).…”
Section: Cell Culture and In Vitro Experimental Designmentioning
confidence: 99%
“…There is growing evidence that ionising radiation shifts the balance between the PAI-1 vs. ID-1 (inhibitor of DNA binding-1) pathways [111] and that PARP-1 is involved in the regulation of the Smads downstream of TGF-β1 in endothelial and vascular smooth muscle cells. In animal models PARP inhibitors have been shown to alleviate fibrotic remodelling of blood arteries by inhibiting the TGF-β/Smad3 pathway [112], high glucose-induced peritoneal epithelial mesenchymal transition (EMT) and fibrosis [113], diabetic or hypertensive cardiomyopathy [114][115][116][117][118] and a variety of syndromes linked to chronic oxidative stress or exaggerated inflammation [119,120]. Taken together, these data suggest that targeting PARP-1 might be a promising therapeutic approach against vascular or pro-fibrotic diseases induced by dysregulation of the TGF-β/Smad3 pathway following irradiation.…”
Section: In Vivo Radiation Sensitivity After Parp Inhibition: Additiomentioning
confidence: 99%